A computer-aided comparative study of progressive alertness changes in nurses working two different night-shift rotas. - Dingley J (Journal of Advanced Nursing (Wiley-Blackwell))
Two groups of nurses were investigated during the course of two different types of night-shift rota. The purpose was to define, if possible, the optimum shift pattern for hospital night staff. The mental alertness of two groups of nurses was assessed, both subjectively and objectively, at the beginning and end of each night-shift of a set of nights being worked. Alertness was assessed subjectively by means of a visual analogue scale, and objectively by means of a computer generated test, the unprepared simple reaction time task. One group worked permanent nights and the other rapidly rotating nights. Subjectively the nurses felt they were more alert at the beginning than at the end of a night-shift, and also at the beginning of a span of nights than at the end. With computer testing, performance was broadly worse at the beginning of a shift than at the end. It was worse at the beginning of a span of nights, improving to a peak at around the fourth day, and then in the case of permanent nights, remaining about the same or deteriorating slightly towards the end of the span. The improvement by day 4 could be a practice effect or it may be that it takes this long to adjust to the new pattern of working as some authors have described. Debate centres around whether nurses should cease working nights just as they have become accustomed to them as in the rapid rotation, or continue for longer to gain benefit from this acclimatization as in permanent nights.